Evaluation of IL-6, FoxP3 Treg lymphocytes, intestinal barrier biomarkers and the use of synbiotics in obese adolescents: a pilot study - Aziz, Cylmara; Morales, Armando; Pinto, Walter; Fanchini, Vanessa; Dell Aquila, Luis; Sangaleti, Carine; Elias, Rosilene; Dalboni, Maria (Frontiers in Pediatrics, 2023)
Aim This prospective pilot study evaluated inflammatory and intestinal barrier biomarkers and the effects of a synbiotic in obese adolescents. Methods Eighteen obese and 20 eutrophic adolescents were evaluated for body composition using bioimpedance analysis (BIA), body mass index (BMI), IL-6 and lipopolysaccharide (LPS) serum levels, CD4 and FoxP3 Treg lymphocytes and monocytes. Synbiotic supplementation for 60 days was also evaluated for these parameters only in obese adolescents. Results We observed an increase in CD4 lymphocyte (18.0 ± 12.4 vs. 8.9 ± 7.5; p < 0.01), IL-6 (0.30 ± 0.06 vs. 0.20 ± 0.06; p = 0.02) and LPS (0.18 ± 0.15 vs. 0.08 ± 0.05; p < 0.01) levels in obese compared to eutrophic adolescents. After synbiotic supplementation, FoxP3 Treg lymphocytes increased (14.0 ± 6.7 vs. 9.9 ± 5.4; p = 0.02) in obese adolescents. Conclusions Obese adolescents presented a state of microinflammation and intestinal barrier breakdown, and synbiotic supplementation increased the expression of FoxP3 Treg lymphocytes, an anti-inflammatory regulator. Whether the increase in FoxP3 Treg lymphocytes may have an impact on inflammation and outcomes in obese adolescents deserves further evaluation.